Trigonometric equations form replace solve about - Gavhar Akhadovna Akhmedova; Tulasheva Surayyoxon Isomiddin qizi (Researchparks Publishing, 2023)
In the process of solving trigonometric equations, when we make some changes of forms or when the left side is replaced by the right side of the formulas given in the article, the solution may disappear. This is why it is important to check the roots that we find when using these formulas.